Pengaruh Model Problem Based Learning Berbantuan Media Audio terhadap Keterampilan Menyimak Siswa Kelas V Sekolah Dasar - Kurniaman, Otang; Sari, Intan Kartika; Hafizah, Hafizah (TSAQOFAH, 2023)
The purpose of this study was to determine the effect of the problem based learning model on the listening skills of fifth grade students at SDN 37 Pekanbaru in the 2022/2023 academic year. This type of research is a non-equivalent control group design involving two classes, namely the experimental class and the control class. The subjects of this study were the VC class as the control class, totaling 25 people and the VE class as the experimental class, totaling 26 people. Researchers conducted learning using the problem based learning model for the experimental class while in the control class the researchers carried out conventional learning. Students' listening skills are measured through listening skills tests in the form of audio. The results showed that the hypothesis tested using the t-test obtained a significance of 0.000 < 0.05, so that Ha was accepted and Ho was rejected. These findings indicate that there is an influence of the Problem Based Learning model on students' listening skills.